Study on Microstructure and Mechanical Properties of Hypereutectic Al–18Si Alloy Modified with Al–3B - Gong, Chunjie (Materials (Basel), 2018)
An hypereutectic Al–18Si alloy was modified via an Al–3B master alloy. The effect of the added Al–3B and the modification temperature on the microstructure, tensile fracture morphologies, and mechanical properties of the alloy were investigated using an optical microscope, Image–Pro Plus 6.0, a scanning electron microscope, and a universal testing machine. The results show that the size of the primary Si and its fraction decreased at first, and then increased as an additional amount of Al–3B was added. When the added Al–3B reached 0.2 wt %, the fraction of the primary Si in the Al–18Si alloy decreased with an increase in temperature. Compared with the unmodified Al–18Si alloy, the tensile strength and elongation of the alloy modified at 850 °C with 0.2 wt % Al–3B increased by 25% and 81%, respectively. The tensile fracture of the modified Al–18Si alloy exhibited partial ductile fracture characteristics, but there were more areas with ductile characteristics compared with that of the unmodified Al–18Si alloy.